PRODUCT DIVERSIFICATION FOR SUSTAINABILITY INSPIRED BY TRADITIONAL ROGAN PRINTING OF GUJARAT - Khalkar, Sakshi; Sadhna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The age-old artistic practice of rag painting, which is practiced in Gujarat, Peshawar, and Sindh. It involves using a stylus to expertly apply a thick paste made of vegetable colours and castor or linseed oil onto fabric. The Persian origin of the term "Rogan" means "oil-based," emphasizing the process of heating and forming castor oil in cold water to create a viscous material. This art form was once quite popular among the Muslim Khatris group in Gujarat, and it is historically credited to the Afridis, a community of Syrian descent. After the first impression, the cloth is carefully folded to create a mirrored design. The artists used their palms to apply body-temperature paint. Rogan painting, which is well-known for its rich colours and intricate designs that frequently incorporate floral themes, animals, and regional cultural features, has faced challenges due to low awareness and the rise of low-cost, automated textiles. However, there has been a resurgence in recent years, contributed to increased tourists, support from non-profits and local cooperatives, and the prestige of winning awards and recognition. This paper gave insights into the ideation of incorporating and being inspired by Rogan art motifs into product diversification with contemporary designs through embroidery for garment collections.